Região metropolitana: governança como instrumento de gestão compartilhada - Pires, Lilian Regina Gabriel Moreira (2016)
The aim of this research was to present a proposal for a practical application model of the interdepartmental governance instrument for Metropolitan Regions. The choice of theme is justified because of the difficulty of the matter in the face of constitutional competencies, as well as the historical neglect of Public Administration with planning as an effective instrument of efficiency and search for equality. Added to this context, is the fact that the complexity of collective life in the metropolis, which is increasingly antagonistic, as far as it produces wealth and increases inequality. The work, considering the interdisciplinarity of the subject, involved research and examination of the doctrine of other areas of knowledge, such as urbanism, sociology, and economics, as well as national legal doctrine and jurisprudence. This project presents the metropolitan fact, besides its affirmation in the legal system of the country. It was also analyzed the federative system and the urban competences. Contextualized the difficulties of metropolitan management, two examples of management are highlighted: water resources and the metropolitan area of Belo Horizonte, presenting at last a model of metropolitan governance, specifically regarding the decision-making body